Flexibility of Timescales of Evidence Evaluation for Decision Making - Ganupuru, Preetham; Goldring, Adam B.; Harun, Rashed; Hanks, Timothy D. (Current biology, 2019)
To understand the neural mechanisms that support decision making, it is critical to characterize the timescale of evidence evaluation. Recent work has shown that subjects can adaptively adjust the timescale of evidence evaluation across blocks of trials depending on context [1]. However, it’s currently unknown if adjustments to evidence evaluation occur online during deliberations based on a single stream of evidence. To examine this question, we employed a change-detection task in which subjects report their level of confidence in judging whether there has been a change in a stochastic auditory stimulus. Using a combination of psychophysical reverse correlation analyses and single-trial behavioral modeling, we compared the time period over which sensory information has leverage on detection report choices versus confidence. We demonstrate that the length of this period differs on separate sets of trials based on what’s being reported. Surprisingly, confidence judgments on trials with no detection report are influenced by evidence occurring earlier than the time period of influence for detection reports. Our findings call into question models of decision formation involving static parameters that yield a singular timescale of evidence evaluation and instead suggest that the brain represents and utilizes multiple timescales of evidence evaluation during deliberation. •Individuals can flexibly adjust the timescale of evaluation of past evidence•Evidence evaluation depends on the type of decision in a change-detection task•Evidence evaluation differs for detection and confidence when no detect report occurs•Confidence of no change depends on longer timescales than change detection Evidence evaluation helps to guide decision making. Ganupuru et al. show that individuals can flexibly adjust the timescale of evaluation of past evidence depending on the type of decision they make. In particular, timescales of evaluation are markedly shorter for change-detection reports than for confidence judgments in which no change has occurred.